Different Nursing Care Methods for Prevention of Keratopathy Among Intensive Care Unit Patients - Kalhori, Reza Pourmirza (Glob J Health Sci, 2016)
BACKGROUND: Patients with reduced consciousness level suffer from eye protection disorder and Keratopathy. This study was conducted to compare effect of three eye care techniques in prevention of keratopathy in the patients hospitalized in intensive care unit of Kermanshah. METHODS: This clinical trial was conducted in 2013 with sample size of 96 persons in three random groups. Routine care included washing of eyes with normal saline and three eye care methods were conducted with poly ethylene cover, liposic ointment, and artificial tear drop randomly on one eye of each sample and a comparison was made with the opposite eye as the control. Eyes were controlled for 5 days in terms of keratopathy. Data collection instrument was keratopathy severity index. Data statistical analysis was performed with SPSS-16 software and chi-squared test, Fisher’s exact test, ANOVA and Kruskal–Wallis one-way analysis of variance. FINDINGS: The use of poly ethylene cover (0.59±0.665) was significantly more effective in prevention of keratopathy than other methods (P=0.001). There was no statistically significant difference between two care interventions of liposic ointment and artificial tear drop (P=0.844) but the results indicated the more effective liposic ointment (1.13±0.751) than the artificial tear drop (1.59±0.875) in prevention of corneal abrasion (P<0.001). CONCLUSION: Results of the study suggest the use of poly ethylene cover as a non-aggressive and non-pharmaceutical nursing and therapeutic method for prevention of keratopathy in the patient hospitalized in intensive care unit.